2021
DOI: 10.4236/ojapps.2021.104034
|View full text |Cite
|
Sign up to set email alerts
|

A Framework Analysis for Lean Transformation: A Case Study of a Public Utility in Greece

Abstract: Purpose: Nowadays, the worldwide economic recession has created numerous challenges in the Public Sector of Greece, which in turn affect the sustainability of public enterprises. Overall, there is a high pressure to increase productivity and reduce operating costs. The need to adapt to the new environment is pushing public organizations to implement Lean Management strategies in accordance with Private Sector standards. However, the limited budget, public deficits and debts, bureaucratic culture, political dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…a total of 1,060 CSCs (Safari et al , 2020; Klein et al , 2022). The e-mail invitation also contained a brief explanation of the purpose of the study, as well as an explicit instruction to the recipient to forward the e-mail to all employees (from all hierarchical levels) of the specific CSC (Madsen et al , 2017; Angelopoulos and Pollalis, 2019; Pollalis and Angelopoulos, 2021). This URL led potential respondents to the questionnaire home page, which provided information on the research objectives, confidentiality and anonymity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…a total of 1,060 CSCs (Safari et al , 2020; Klein et al , 2022). The e-mail invitation also contained a brief explanation of the purpose of the study, as well as an explicit instruction to the recipient to forward the e-mail to all employees (from all hierarchical levels) of the specific CSC (Madsen et al , 2017; Angelopoulos and Pollalis, 2019; Pollalis and Angelopoulos, 2021). This URL led potential respondents to the questionnaire home page, which provided information on the research objectives, confidentiality and anonymity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Gupta et al (2016) found no available literature presenting the success measures of Lean development in service organizations (public or private). In other words, the issue of Lean adoption in the public sector remains largely under review (Juliani and de Oliveira, 2021; Fredriksson, 2020; Pollalis and Angelopoulos, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019b). According to Juliani and de-Oliveira (2017) and Pollalis and Angelopoulos (2021) there is a severe deficiency of bibliography and worldwide practice regarding the CSFs of lean management in public service sector.…”
Section: Introductionmentioning
confidence: 99%
“…The review of previous studies on lean in the Greek context showed that Lean is used in various parts of the Greek public sector and the concept has been adopted and implemented quite extensively in the municipal sector. More specifically, Angelopoulos and Pollalis (2019) and Pollalis and Angelopoulos (2021) investigated the effect of CSFs of lean adoption in Greece public companies and in particular in public utility organizations that specialize in renewable energy sources (eg power, water, etc.) while Psomas and Antony (2018) evaluated the degree of adoption of lean principles in a wide variety of Greek public service organizations such as municipalities, organizations of ministries and central government, educational institutions etc.…”
Section: Introductionmentioning
confidence: 99%